The film - Jackson-Wrigley, M. (Maurice), 1886-1972; Briscoe, Walter A. (Walter Alwyn), 1878-1934; Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Film: Its Use in Popular Education" by M. Jackson-Wrigley is a scientific publication written in the early 20th century. This work explores the educational potential of film as a tool for enhancing learning across various subjects, advocating for its inclusion in educational settings and libraries. Wrigley emphasizes the significant role that cinema can play in making education more engaging and effective. The opening of the book presents a foreword by Sir Gilbert Parker, highlighting the undeniable benefits of using films to teach subjects like geography, science, and literature across schools. It includes discussions on the historical development of motion pictures and their recognition as valuable educational aids. Wrigley's preface states the intention to compile previously shared thoughts on the topic, showcasing how films can captivate students' attention and facilitate learning by bridging traditional textbooks with visual storytelling. The introduction further reinforces the idea that film has not yet reached its full potential in education, urging readers to recognize its transformative power in the classroom. (This is an automatically generated summary.)
Release date is 2023-09-27
Charlene Taylor, David E. Brown, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Education; Motion pictures in education